Representasi Kuliner Tradisional Nusantara dalam Novel Nonik Jamu Karya Rina Suryakusuma: Kajian Gastrokritik - Firmansyah, M Ryan; Setyoningrum, Vita Diah; Nuraini, Dewi; Amalia, Rizka (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
This study analyzes the representation of traditional Nusantara cuisine in the novel Nonik Jamu (2024) by Rina Suryakusuma using a gastro-critical approach enriched with semiotic analysis. The analysis focuses on three main aspects: (1) how traditional Nusantara cuisine is represented in the novel; (2) how traditional Nusantara cuisine reflects social and cultural values; and (3) how traditional Nusantara cuisine contributes to the formation of character identity. The findings show that traditional Nusantara cuisine functions not only as a narrative element but also as a medium of complex cultural representation. The results include: (1) the representation of traditional Nusantara cuisine through processes of preparation, presentation, and consumption; (2) the presence of social and cultural values; and (3) traditional Nusantara cuisine as a means of shaping character identity. This study contributes to the development of literary gastronomy in Indonesia, particularly in understanding the relationship between traditional Nusantara cuisine, culture, and identity within literary texts.